Apex Managerial Approach towards Various Proportions of Holistic Marketing Interactions - Gautam, Amit; Johri, Gyanendra B. S. (Indian Journal of Marketing, 2009)
Fusion of business and academic platforms do not provide sufficient mechanism regarding implementation technique for effective involvement of apex managerial agencies towards holistic marketing interactions. On the other hand need of the hour is that not only apex managerial approach but every employee’s approach towards holistic marketing interactions or technically integrated marketing communications must be well defined and should work on a pre defined system. Through this paper we provide a model for apex managerial approach towards various proportions of holistic marketing interactions. This empirical research depicts the fact very emphatically that increasing participation of apex managerial agencies in marketing interactions could be positively associated with holistic marketing interactions.